EKSPLORASI SPASIAL CENDAWAN TANAH PADA SEKITAR RHIZOSFER TANAMAN JAMBU METE (Anacardium occidentale L.) DI KARANGASEM DAN BULELENG-BALI - Wulandari, Ni Luh Desy; Proborini, Meitini W.; Sundra, I Ketut (SIMBIOSIS; Vol I, No 2, Tahun 2013, 2013)
Research have been carried out to calculate total colony of fungi, determine fungi species, and the rate spread of the fungi in rhizosphere a cashew plantations (Anacardium occidentale L.) at Sukadana Karangasem and Sendang Buleleng for 4 months (October 2012 - January 2013). Samples were taken from two different areas in which five point were sampled. Results data were analyzed qualitatively by identifying the species of fungi that is a description. The quantitative data was taken to calculate total colony of fungi. The research found 11 species of fungi taken from two different locations, namely: Aspergilus flavus, A. niger, A. parasiticus, Botrytis cinera, Cladosporium sphaeospermum, Fusarium sporotrichioides, P. brevicompactum, P. citrinum, P. chrysogenum, Rhizopus stolonifer, and Synchephalastrum racemosum. Total fungal colony in Sukadana Karangasem was : 33.6 x 103 - 35 x 103 CFU /g, in Sendang Buleleng 22.6 x 103 – 37.6 x 103 CFU/g. Abundance of fungi in Sukadana Karangasem is relatively uniform (0.85) and in Sendang Buleleng belong to cluster (1,03). Keywords: Cashew rhizosphere, abudance of fungal species, Karangasem, Buleleng- Bali